Exploring Meditation Influence on Stem Cell: A Review of Current Evidence - Santosa, I Gusti Ngurah Putra Eka; Jawi, I Made; Bakta, I Made; Yasa, I Wayan Putu Sutirta; Wirawan, I Made Ady; Lesmana, Cokorda Agung Bagus Jaya; Kandarini, Yenny; Purnamawati, Susy (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2024)
Endogenous stem cells play a critical role in maintaining tissue homeostasis, repair, and regeneration. The interconnectedness of mind and body has long been recognized as influencing physical health, with practices such as yoga and meditation demonstrating positive effects on overall well-being. This review aims to synthesize current evidence on the effects of meditation on stem cell function, focusing on both indirect (telomere-related) and direct pathways. Meditation appears to influence stem cell function through various mechanisms. Indirectly, meditation may impact stem cells by modulating telomere length and activity. This modulation is likely mediated through stress reduction, modulation of the hypothalamic-pituitary-adrenal (HPA) axis, melatonin elevation, immune system modulation, and reduction of oxidative stress. Directly, meditation may influence stem cell trafficking and differentiation. While studies suggest potential benefits of meditation on stem cell function, further research is needed to fully elucidate the underlying mechanisms. Emerging evidence suggests that meditation may positively influence stem cell function through both indirect and direct pathways. Future research should focus on clarifying the precise mechanisms, investigating the role of meditation parameters, and conducting clinical trials to assess the therapeutic potential of meditation in promoting stem cell-mediated tissue regeneration and repair. A multidisciplinary approach involving researchers from various fields is crucial for comprehensively understanding the complex interplay between meditation, stem cells, and overall health.